Information and Communication Technology Approaches and Multimedia Authoring Skills of Public Elementary School Teachers - Richard Mendoza Bañez; John Louie Vergara Yedra (Universitas Negeri Makassar, 2019)
This descriptive-explanatory research determined the extent of utilization of ICT approaches in performing teaching-related tasks and self-assessment of multimedia authoring skills of 162 public elementary school teachers at Tanauan City North District, Philippines. Utilizing a researcher-made questionnaire in gathering the needed data and applying appropriate statistical tools, the results of the study revealed that the respondents highly utilized technology literacy approach, and utilized both knowledge deepening, and knowledge creation approaches in performing teaching-related tasks as they integrate technology into the curriculum, utilize spreadsheet in monitoring pupils’ learning progress, and use available ICT resources to help pupils acquire and demonstrate complex cognitive skills. The respondents were also found to be competent in media literacy, using music and arts, design principles, creativity and novel thinking, and considering audiences as components of multimedia authoring skills that was likely to be influenced by their utilization of ICT approaches as affirmed by the significant relationship identified between the two variables. This study calls for pedagogical innovations by capacitating public elementary school teachers with multi-media authoring skills through ICT-skill enhancement program.